2010
DOI: 10.1097/brs.0b013e3181bb4f21
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anatomical Variations of Vertebral Artery in C2 Vertebra With Magnetic Resonance Imaging and Its Application in the C1–C2 Transarticular Screw Fixation

Abstract: The 3D CISS MRI with isometric voxels is a safe and simple imaging technique to outline the vertebral arteries in C2. Reconstruction images are easily created and undistorted. It is one of the useful imaging in preoperative planning of transarticular screw fixation and determination of anatomy of vertebral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…From the biomechanical viewpoint, techniques using screws are superior to the wiring technique but have the disadvantage of the risk of injury to the vertebral artery, spinal cord and roots. 1,4-7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the biomechanical viewpoint, techniques using screws are superior to the wiring technique but have the disadvantage of the risk of injury to the vertebral artery, spinal cord and roots. 1,4-7 …”
Section: Discussionmentioning
confidence: 99%
“…One of the main aspects in relation to the anatomy of C1-C2 is the location of the vertebral artery, 1 which runs through the transverse foramen of C1, looping on both sides in the posteromedial direction up to its point of entry in the occipital foramen. This structure, therefore, is at risk during the passage of screws in both vertebrae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Harms technique [6] uses polyaxial screws applied to the lateral mass of the atlas and the pedicles of the axis connected via bilateral rods. Both techniques are technically demanding and carry a risk of vertebral artery injury, especially in aberrant courses, which occur in up to 23% of all cases [11]. The surgeon is manually limited by the small dimension of the C2 pedicle.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 12% of patients were considered at risk with unilateral anatomic variation, and another 6% were not suitable for screw fixation because of bilateral variation. In 2010, a three-dimensional CISS magnetic resonance imaging study 5 demonstrated that 40% of patients had significant anatomic variations on at least one side, prohibiting the insertion of transarticular screws. In another recent report, comprehensive computed tomography evaluation showed that the AA joint demonstrated larger variability in general, particularly in the sagittal plane.…”
Section: Anatomic Perspectivesmentioning
confidence: 99%